Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.vaccine.2006.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Protective avian influenza in ovo vaccination with non-replicating human adenovirus vector

Abstract: Protective immunity against avian influenza virus was elicited in chickens by single-dose in ovo vaccination with a non-replicating human adenovirus vector encoding an H5N9 avian influenza virus hemagglutinin. Vaccinated chickens were protected against both H5N1 (89% hemagglutinin homology; 68% protection) and H5N2 (94% hemagglutinin homology; 100% protection) highly pathogenic avian influenza virus challenges. Mass-administration of this bird flu vaccine can be streamlined with available robotic in ovo inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 25 publications
0
59
0
1
Order By: Relevance
“…Immunization and highly pathogenic H5N1 challenge study. In ovo vaccination of 18-day-old embryonated specific-pathogen-free chicken eggs was performed as described previously (45). Briefly, the eggs were candled, and a small hole was made through the air cell with a drill.…”
Section: Vol 81 2007mentioning
confidence: 99%
“…Immunization and highly pathogenic H5N1 challenge study. In ovo vaccination of 18-day-old embryonated specific-pathogen-free chicken eggs was performed as described previously (45). Briefly, the eggs were candled, and a small hole was made through the air cell with a drill.…”
Section: Vol 81 2007mentioning
confidence: 99%
“…However, the intense stress caused by injection could hamper the animal's growth (34). Thus, many investigators are pursuing more convenient and economical avenues for construction of new vaccine candidates, such as recombinant subunit vaccines using baculovirus (28), plasmid DNA (3), or replication-incompetent adenovirus (rAd) (26,27) vectors. The H5N1 strain can infect animals through their respiratory and intestinal tracts (10).…”
mentioning
confidence: 99%
“…In breeders and layers, it would be more acceptable, since vaccine traces are not expected to be detected in eggs and offspring. Toro et al described an interesting vaccination technology that proposed the use of robotic injectors for in ovo immunization of an adenovirus-based vaccine encoding the H5N9-derived hemag- (28,29). Therefore, we also tested the in ovo immunization route for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicated that the in ovo route of administration can be effective, with the potential to provide an easy and rapid way to immunize a large number of eggs with an adenovirus-based vaccine via robotic in ovo injectors (1,29). Different doses of Ad5.HA (10 7 to 10 10 ) or Ad5 (control) vaccine were injected into the allantoic cavity of 18-day-old embryonated chicken eggs.…”
Section: Route Of Administration Of the Ad5ha Vaccine In Chickensmentioning
confidence: 99%